Fatty Acids of European Sardine (Sardina pilchardus) White Muscle Can Discriminate Geographic Origin Along the Iberian Atlantic Coast - Ricardo Calado; Marcos Palma; Maria Rosário Domingues; Fernando Ricardo; Felisa Rey (Foods)
The European sardine (Sardina pilchardus) ranks among the most valuable species of Iberian fisheries, and the accurate tracing of its geographic origin, once landed, is paramount to securing sustainable management of fishing stocks and discouraging fraudulent practices of illegal, unreported, and unregulated (IUU) fishing. The present study investigated the potential use of S. pilchardus white muscle fatty acids (FAs) to successfully discriminate the geographic origin of samples obtained in seven commercially important fishing harbors along the Iberian Atlantic Coast. While 35 FAs were identified using gas chromatography–mass spectrometry in the white muscle of S. pilchardus, the following, as determined by the Boruta algorithm, were key for sample discrimination: 14:0, 22:6n-3, 22:5n-3, 18:0, 20:5n-3, 16:1n-7, 16:0, and 18:1n-7 (in increasing order of relevance). An average 83% correct allocation of landed specimens was achieved, with some landing locations presenting 100% correct allocation (e.g., Ría de Pontevedra in northern Spain and Peniche in central Portugal). Linear discriminant analysis revealed a separation of samples from northern Spain and Peniche, and a partial overlap of all other locations. The present results highlight the potential of using FAs of S. pilchardus white muscle to reliably discriminate the geographic origin of landed individuals along the Iberian Atlantic coast.